Gastrointestinal sutures: Comparative study of intestinal anastomoses in one plane - Campos, Nestor; Mesa Figueras, Guillermo; Camacho, Maria Del Carmen; Camacho, Graciela (Cirugía del Uruguay, 1971)
This is a comparative study of two types of intestinal suture on a monoplane: one, extramucosa, edge to edge; and the other with eversion of the mucous membrane. The case history is formed by 84 cases of intestinal sutures, divided into two series. Results favour markedly the etxramucosa monoplane suture, which presented the lower death rate, lower incidence of suture failures and lower frequency of complex adherences, plus no stenosis